Endoscopic third ventriculostomy complications: avoidance and management in a stepwise manner - Ahmed A. Farag; Faisal A. Asiri; Mohamed A. Khoudir; Mofareh Ismaeel; Waeel Hamouda; Islam M. Alaghory; Rana H. Moshref (Egyptian Journal of Neurosurgery, 2022)
Abstract Background Various complications of endoscopic third ventriculostomy (ETV) have been described. One has to recognize these complications and learn how to avoid them. Methods We performed a literature review regarding the reported complications of ETV procedures discussed in a correlated manner with the surgical steps. Furthermore, we reviewed the technical notes described by experienced neuroendoscopists, including surgical indications, choice of the endoscopic entry point and trajectory, anatomic orientation, proper bleeding control and tight closure, to prevent and deal with such complications. Results and conclusion A lesson learned that comprehensive knowledge of ventricular anatomy with proper orientation by studying the preoperative images is mandatory and one should be aware of all complication types and rates.